Fish oil ameliorates ethanol-induced gastric injury in rat by modulating gene related to apoptosis - Nikoo Parham; Kaveh Rahimi; Zohreh Ghotbeddin; Mohammad Reza Tabandeh (Scientific Reports, 2024)
Abstract Gastric ulcers are a type of digestive disease that can severely affect a person's quality of life. Our study aimed to investigate the effects of fish oil on ethanol-induced gastric ulcers in rats, with the purpose of providing more comprehensive information on the topic. The study looked at various factors such as gastric ulcer index, and nitric oxide (NO) levels in stomach tissue. To investigate apoptosis, the mRNA levels of Bax, Bcl-2, and Caspase 3 were analyzed. The results showed that fish oil can reduce gastric acidity and the gastric ulcer index in cases of ethanol-induced gastric ulcers. It was found that fish oil can increase NO levels and improve the anti-apoptotic system by increasing the expression of Bcl-2 while decreasing the expression of Bax and Caspase 3. In general, the study demonstrates that fish oil can protect the stomach from ethanol-induced damage by reducing the apoptosis pathway via nitric oxide.